Systematic Review of Mixed Studies on Malaria in Pregnancy: Individual, Cultural and Socioeconomic Determinants of Its Treatment and Prevention (2022)
ABSTRACT: Malaria in pregnancy (MiP) is a global public health problem; its research is predominantly quantitative. The objective was to analyze the individual, cultural and socioeconomic determinants of the treatment and prevention of MiP with a systematic review of mixed studies (search had no date restriction). Reproducibility and evaluation of the methodological quality were guaranteed. 21 studies were included (20 from Africa). The quantitative component included 7816 pregnant women and 483 health workers. The qualitative component included 800 subjects (pregnant women, health workers, family members and community leaders). The main topics were the use and acceptability of WHO strategies to prevent MiP, individual determinants related with knowledge, perceptions, attitudes and behaviors on MiP, and cultural and socioeconomic barriers for its treatment and prevention. The main determinants of MiP were long distance to the clinic, lack of economic resources, low-coverage antenatal care, few health workers in the communities, drug shortages, cultural rules that prevent women's participation in health issues, and misconceptions about MiP. MiP has determinants related to economic conditions, the structure and functioning of the health system, symbolic and cultural aspects, as well as knowledge, beliefs, perceptions and behavior of pregnant women, which prevent optimal access and use of preventive strategies. This study evidences the importance of intersectional, intersectoral, and interdisciplinary work to prevent MiP.